2017
DOI: 10.1155/2017/5314649
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Regulates Cell Viability and Invasion in Esophageal Squamous Cell Carcinoma through the miR-129/CTBP2 Axis

Abstract: Background Long noncoding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) was reported to be aberrantly upregulated and promote esophageal squamous cell carcinoma (ESCC) cell progression. Nevertheless, the molecular mechanism of NEAT1 involved in the competing endogenous RNA (ceRNA) regulatory network in ESCC progression remains poorly defined. Methods The expressions of NEAT1, miR-129, and C-terminal-binding protein 2 (CTBP2) in ESCC cells were examined by qRT-PCR. The effects of NEAT1 knockdown and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…The striking enrichment of NRAD1 in basal-like breast cancer and TNBC suggests that NRAD1 may serve as an attractive diagnostic or prognostic target. In agreement with previous reports [122,123], our analysis also showed that NEAT1 and MALAT1 were enriched in ER+ breast cancers. This conflicts with other studies that have shown that these lncRNAs are TNBC-enriched [64,67].…”
Section: Are Breast Csc-associated Lncrnas Enriched In Tnbcs/basal-lisupporting
confidence: 93%
“…The striking enrichment of NRAD1 in basal-like breast cancer and TNBC suggests that NRAD1 may serve as an attractive diagnostic or prognostic target. In agreement with previous reports [122,123], our analysis also showed that NEAT1 and MALAT1 were enriched in ER+ breast cancers. This conflicts with other studies that have shown that these lncRNAs are TNBC-enriched [64,67].…”
Section: Are Breast Csc-associated Lncrnas Enriched In Tnbcs/basal-lisupporting
confidence: 93%
“…Besides, NEAT1 sponged miR-124 in neuroblastoma [37], retinoblastoma [38], Alzheimer's disease [38] and nasopharyngeal carcinoma [39]. Furthermore, NEAT1 sponged miR-129 in esophageal squamous cell carcinoma [40] and hepatoblastoma [41]. NEAT1 also sponged miR-335 in hepatocellular carcinoma [42], acute lymphoblastic leukemia [43], gastric cancer [44] and pancreatic cancer [45].…”
Section: Discussionmentioning
confidence: 99%
“…As known, lncRNAs can negatively regulate microRNAs (miRNAs), which can depress their miRNA targets (Xia et al, ). For example, NEAT1 can regulate esophageal squamous cell carcinoma (ESCC) progression through miR‐129/CTBP2 (Li, Chen, Gao, Li, & Shi, ). NEAT1 promotes HCC development by regulating miR‐129‐5p (Fang et al, ).…”
Section: Discussionmentioning
confidence: 99%